Prediction of shrink lines in powder bed fusion of metals using a laser beam by means of a finite element simulation approach - Dominik Rauner; Niklas Eilers; Hannes Panzer; Lukas Frei; Michael F. Zaeh (Journal of Advanced Joining Processes)
Powder bed fusion of metals using a laser beam (PBF-LB/M) enables the near-net-shape fabrication of thin-walled parts with a high geometric complexity, thus often featuring structural transitions. Due to high temperature gradients during manufacturing, these structural transitions are subject to localized deformations, which manifest themselves in a shrink line, which is reducing the part lifetime and the dimensional accuracy. In current PBF-LB/M process simulations, however, the shrink line formation cannot be predicted on a physical basis yet. In this study, a finite element approach for efficiently predicting the shrink line formation is presented. The three-stage approach begins with a numerical geometry analysis, which is used to define an appropriate finite element mesh for the subsequent analyses. This is followed by the prediction of the geometry-dependent overheating during the PBF-LB/M process. Using these overheating results and an experimentally calibrated overheating-shrink-line relation, the shrink lines are modeled in a mechanical analysis considering the physics-based effects. The simulation approach was verified on an academic specimen design and was experimentally validated on two parts with different degrees of geometric complexity. The derived overheating-shrink-line relation provided a valid strategy for predicting the resulting shrink line depth. Applying the approach, the deviation between the measurements and the shrink line simulation was determined to be lower than 41 µm. Furthermore, the prediction quality of the dimensional accuracy was increased by 6.9 % for a topology-optimized part. For the approach, necessary extensions were derived to allow for simulating an asymmetric shrink line formation in the future.